D-Dimer As A Parameter Of Disease And Death Of Covid-19 Patients In Islamic Hospital, Surabaya - Muzaijadah Retno Arimbi; Intan Nurani Indrajanu; Pratika Yuhyi Hernanda (Universitas Wijaya Kusuma Surabaya, 2024)
Background: Previous studies of Community Associated Pneumonia (CAP) and Chronic Obstructive Pulmonary Disease (COPD), patients have shown that D-Dimer increases higher in severe cases and can be used as a prognostic biomarker and whilst D-Dimer> 1 mcg/ ml tends to be death for hospitalized adult patient with a diagnosis of Covid-19. However, D-Dimer's role in Covid-19 patients has not been fully studied. We aim to conduct research on D-Dimer as a parameter of Clinical Severity and Death of Covid-19 Patients in Islamic Hospital, in Surabaya. Methods: This type of research is an analytic observational study with a retrospective approach. The population in this study were all patient’s data retrieved from the Dahlia Room’s database from June to July 2020 which were taken through EMR (an Electrical Medical Records) from a total of 189 patients with the total sample of 82 patients. Data analysis in this study used chi-square (X2) with a significant value of p <0.05. Results: Age over 60 years is associated with a higher risk of severe Covid-19 infection (P<0.05). A history of hypertension significantly affects the severity of Covid-19 infection (P < 0.05). The proportion of recoveries (53.7%) was higher than the number of deaths (46.3%), although the majority of patients experienced severe clinical severity (39%). Laboratory parameters, such as D-dimer values, correlated significantly with patient age (P = 0.027, <0.05). Conclusion: The study highlights the importance of factors such as age and history of comorbid diseases in predicting the severity of Covid-19 infection. A better understanding of these risk factors can help in more effective management and management of Covid-19 patients.